ANALISIS PENERAPAN PENGETAHUAN KARAKTER DALAM PEMBELAJARAN PKN UNTUK MEMBENTUK SIKAP KEDISIPLINAN SISWA KELAS III DI UPTD SD NEGERI SEPULUH 01 - Putri, Arini Diana; Hariyani, Yunita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores how the implementation of character knowledge in Civic Education (Pkn) influences the discipline of third-grade elementary school students. The research employs a qualitative approach, using observation, documentation, and interviews as data collection methods. The findings reveal that the application of character knowledge is carried out through habituation, role modeling, and the integration of character values within Pkn learning. From the perspective of student discipline, there has been noticeable improvement; however, students still require continuous guidance. Teachers play a crucial role in fostering students’ discipline by providing examples, guidance, and reinforcement.